Blended Learning in Inclusive Education: Experienced Teacher's Voices - Tri Retna Astari; Nur Hidayanto Pancoro Setyo Putro (AL-ISHLAH: Jurnal Pendidikan, 2023)
Since the COVID-19 pandemic, many schools have implemented blended learning, where learning is held online and offline. The use of blended learning is considered effective but the application of blended learning will still be the same when applied to inclusive classes where there are not only regular students but also students with special education needs (SEN). The purpose of this research is to better understand teachers' perspectives on blended learning activities in English classrooms, as well as perceived barriers and problems, also in this research, was to tell a story. To know how EFL teacher experiences when teaching in an inclusive classroom the researcher interviewed an EFL secondary school teacher. The findings suggest that the effectiveness of inclusive education implementation is dependent on teachers' instructional approaches, learning resources, and institutional and governmental support. Her perspectives on inclusive education were critical in teaching people about special education students and changing attitudes while dealing with both regularly developing and disabled students. The financial position of the student's families is one of her ongoing difficulties as she tries to adopt blended learning in the inclusive classroom. She had vowed to investigate blended learning and find methods to include it in regular courses or inclusive classes.